Clonal hematopoiesis and acute myeloid leukemia - A. I. Kashlakova; B. V. Biderman; E. N. Parovichnikova (Онкогематология, 2023)
During aging phenotypic changes in the hematopoietic system occur, and possible reason of these changes can be accumulation of gene mutations in hematopoietic stem cells or early blood progenitors. Although these mutations are mostly neutral, some may give hematopoietic stem cells and progenitor cells a proliferative advantage. In this case clonal hematopoiesis will arise, which is characterized by the formation of a genetically distinct subpopulation of blood cells. Clonal hematopoiesis may become a basis for the development of hematologic malignancies, such as acute myeloid leukemia. Clonal hematopoiesis associated genes which are most commonly mutated in acute myeloid leukemia patients are DNMT3A, TET2 and ASXL1. The prognostic significance of these gene mutations currently remains a subject of study.